The Brent Goose in the Soviet Union - Uspenski, S M (Wildfowl, 1960)
Owing to the rapid decline in the numbers of Brent Geese over large areas of Europe, Asia and North America, ever increasing attention has been paid to this goose in recent years. It has been recorded that during the past 40-50 years the numbers both of Eurasian (B.b. bernicla) and the American (B.b. nigricans) Brent Geese have sharply declined. The Atlantic Brents (B.b. hrota) are little better off, although they are protected at the places where they nest and at those where they moult and also at their main wintering sites (Salomonsen, 1955). Information is lacking regarding the status of the population of the Eastern Siberian Brents (B.b. orientalis), but such observations as have been made give evidence of a considerable decline of these birds also. The International Committee for Bird Protection stated in 1954 that the Brent Goose is threatened with extinction and approached the governments of all interested states with an invitation to participate in full and universal protection of this species.